Identity Processes and Statuses in Patients with and without Eating Disorders. (27th October 2016) - Verschueren, Margaux; Luyckx, Koen; Kaufman, Erin A.; Vansteenkiste, Maarten; Moons, Philip; Sleuwaegen, Ellen; Berens, Ann; Schoevaerts, Katrien; Claes, Laurence
Abstract: Problems with identity formation are associated with a range of psychiatric disorders. Yet, the mechanisms underlying such problems and how they are refined into specific diagnostic presentations require further investigation. The present study investigated identity processes among 123 women with eating disorders (ED) and age‐matched community controls via a newly developed identity model. Several clinical outcome variables were assessed. Patients with ED scored lower on committing to and identifying with identity‐related choices and scored higher on maladaptive or ruminative exploration, identity diffusion and identity disorder. They also experienced less identity achievement as compared with controls. The identity disorder status was associated with the highest scores on anxiety, depression, borderline personality disorder symptoms, and non‐suicidal self‐injury and the lowest scores on need satisfaction. Results indicate that patients with ED experience more identity problems than community controls and those captured by an identity disorder status experience the most problematic psychosocial functioning. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.